Adhesive application on particleboard from natural fibers: A review. Issue 11 (25th August 2020) - Owodunni, Amina Adedoja; Lamaming, Junidah; Hashim, Rokiah; Taiwo, Owolabi Folahan Abdulwahab; Hussin, Mohd Hazwan; Mohamad Kassim, Mohamad Haafiz; Bustami, Yazmin; Sulaiman, Othman; Amini, Mohd Hazim Mohamad; Hiziroglu, Salim
Abstract: Impending health challenges in the formulations of particleboards from cellulosic‐based waste particles such as wood chips, sawdust, and veneer boards are of great concern. These wastes are majorly bonded together with synthetic resin or binder in the presence of heat and pressure to produce particleboards of various specifications and sizes depending on the end‐use. The qualities of the particleboards depend on the modification of the particle geometry, resin levels, board density, and manufacturing processes. The addition of special additives to enhance the qualitative performance of particleboards such as dimensional stability, fire retardancy enhancement, and moisture resistance is included in the manufacturing process. The milestone in the use of wood particles for particleboard manufacture is the large reduction in the environmental hazard that these abundant wastes cause. Furthermore, this review reports recent research efforts in the use of green adhesives to reduce the health threat related to utilizing formaldehyde‐based particleboard. The use of adhesives produced from natural sources has contributed toward the reduction in the impending health challenges and the cost of building construction by using such a particleboard. Abstract :